Enhancing the Tourism Operation Success in Sabah Malaysia: a Conceptual Framework - Danting, Zou; Quoquab, Farzana; Mahadi, Nomahaza (International Journal of Engineering and Technology, 2018)
In recent years, the tourism industry is in the rise and contributes significantly in the economy of Malaysia. Although Sabah is one of the main tourism attractions in Malaysia, the studies towards the factors that can ensure the tourism operation success have not been fully concerned at the same time. Considering this, the present study proposes a conceptual framework that addresses internal as well as external factors towards the tourism operation success in Sabah. This study utilized scientific way of reviewing literature in gathering the relevant information. Relevant articles are reviewed pertaining to the tourism operation success. Content analysis approach is considered to analyse the data. The framework suggests that, the internal and external issues faced by the tourism operators are the key factors that determined the successful performance and development of the tourism operators in Sabah. The proposed internal factors are proper cash flow management, human resource management and brand image whereas, the external factors are the usage of online social media and the cooperation from the online travel agencies. Together, these two big forces (internal and external) enhance the performance of tourism operations in Sabah which eventually contributes to the tourism operation success.Â Â